Solve all your doubts with Teachoo Black (new monthly pack available now!)

Are you in **school**? Do you **love Teachoo?**

We would love to talk to you! Please fill this form so that we can contact you

Miscellaneous

Misc 1
Deleted for CBSE Board 2023 Exams

Misc 2 Deleted for CBSE Board 2023 Exams

Misc 3 Important Deleted for CBSE Board 2023 Exams

Misc 4 Deleted for CBSE Board 2023 Exams

Misc 5 Deleted for CBSE Board 2023 Exams

Misc 6 Important Deleted for CBSE Board 2023 Exams

Misc 7 Important

Misc 8

Misc 9

Misc 10 Important

Misc 11

Misc 12 You are here

Misc 13

Misc 14 Important

Misc 15 Deleted for CBSE Board 2023 Exams

Misc 16 Important Deleted for CBSE Board 2023 Exams

Misc 17

Misc 18

Misc 19 Important

Misc 20

Misc 21 (i) Important Deleted for CBSE Board 2023 Exams

Misc 21 (ii) Deleted for CBSE Board 2023 Exams

Misc 22 Important Deleted for CBSE Board 2023 Exams

Misc 23 Important Deleted for CBSE Board 2023 Exams

Misc 24 Deleted for CBSE Board 2023 Exams

Misc 25 Important Deleted for CBSE Board 2023 Exams

Misc 26 Deleted for CBSE Board 2023 Exams

Misc 27 Deleted for CBSE Board 2023 Exams

Misc 28 Important Deleted for CBSE Board 2023 Exams

Misc 29 Important

Misc 30 Deleted for CBSE Board 2023 Exams

Misc 31 Important

Misc 32 Important Deleted for CBSE Board 2023 Exams

Last updated at Dec. 8, 2016 by Teachoo

Misc 12 The sum of the first four terms of an A.P. is 56. The sum of the last four terms is 112. If its first term is 11, then find the number of terms. Let the first four terms of A.P. be a, a + d, a + 2d, a + 3d Given, First term = a = 11 Let common difference = d Also given that, Sum of first four term is 56 a + (a + d) + (a + 2d) + (a + 3d) = 56 11 + (11 + d) +(11 + 2d) +(11 + 3d) = 56 11 + 11 + 11 + 11 + d + 2d +3d = 56 44 + 6d = 56 6d = 56 – 44 6d = 12 d = 12/6 d = 2 Hence common difference d = 2 Last four terms are an, an – 1, an – 2, an – 3 We know that nth term of AP = a + (n – 1)d an = a + (n – 1)d Putting values a = 11 & d = 2 an = 11 + (n – 1)2 For an – 1 Putting n = n – 1 in (1) an – 1 = 11 + (n – 1 – 1)2 = 11 + (n – 2)2 For an – 2 Putting n = n – 2 in (1) an – 2 = 11 + (n – 2 – 1)2 an – 2 = 11 + (n – 3)2 For an – 3 Putting n = n – 3 in (1) an – 3 = 11 + (n – 3 – 1)2 an – 3 = 11 + (n – 4)2 It is given that sum of last four term is 112 i.e. an + an – 1 + an – 2 + an – 3 = 112 Putting values from (1), (2), (3), & (4) 11 + (n – 1)2 + 11 + (n – 2)2 + 11 + (n – 3)2 + 11 + (n – 4)2 = 112 11 + 11 + 11 + 11 + (n – 1)2 + (n – 2)2 + 11 + (n – 3)2 + (n – 4)2 = 112 44 + 2[n – 1 + n – 2 + n – 3 + n – 4] = 112 44 + 2[n + n + n + n – 1 – 2 – 3 – 4] = 112 44 + 2 [4n – 10] = 112 2 [4n – 10] = 112 – 44 2 [4n – 10] = 68 4n – 10 = 68/2 4n = 34 + 10 4n = 44 n = 44/4 n = 11 Hence number of terms is 11